2014
DOI: 10.2478/s11536-013-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of stress urinary incontinence and vaginal prolapse for the woman with epispadia

Abstract: AbstractPatient K.L., 32 years old. Menses started at thirteen years old, C 5/28. Patient had two vaginal deliveries in 2004 and 2010. Dysplasia cervicis uteri CIN2-3 was diagnosed in 2007, subsequently diathermoconisation cervicis uteri was performed. The woman was born with epispadia — extrophia of urethra to abdominal wall, without pubic bone. At the age of 8 she underwent an operation in Moscow. During the operation the neck of the bladder was formed as well as urethra, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…These studies are fraught with many confounding variables including heterogeneity in outcomes metrics published (eg, sparse data on ISS, GCS, maternal vital signs, and other baseline characteristics such as comorbidity profiles). Unfortunately, we found that larger databases and registries either have not parsed GSW data from other forms of penetrating trauma [62][63][64][65][66][67] or have inextricably bundled gestational ages. [68][69][70] In the absence of large registries whose data fit predefined inclusion and exclusion criteria, remaining available data effectively resulted in systematically reviewing individual cases.…”
Section: Discussionmentioning
confidence: 95%
“…These studies are fraught with many confounding variables including heterogeneity in outcomes metrics published (eg, sparse data on ISS, GCS, maternal vital signs, and other baseline characteristics such as comorbidity profiles). Unfortunately, we found that larger databases and registries either have not parsed GSW data from other forms of penetrating trauma [62][63][64][65][66][67] or have inextricably bundled gestational ages. [68][69][70] In the absence of large registries whose data fit predefined inclusion and exclusion criteria, remaining available data effectively resulted in systematically reviewing individual cases.…”
Section: Discussionmentioning
confidence: 95%